KERJASAMA PKBM NURHIDAYAH DENGAN PEMERINTAH DESA SUKMULYA SEBAGAI UPAYA MENINGKATKANPARTISIPASI WARGA BELAJAR - Neneng Nurmalasari; Aslih Wahidin, Dede Nuryani, Dede Sandy Noer Fauzi, Miftahul Zamil (JOURNAL OF COMMUNITY DEDICATION, 2022)
One of the non-formal education services needed by Sukamulya Village is in the form of a Community Learning Activity Center (PKBM) designed to meet community needs. The collaboration between PKBM and the village government in increasing community participation in education is an interesting matter to study because it relates to the low level of education in the village community. This study uses the PAR (Participatory Action Research) method. The process of building cooperation to increase community participation is carried out through the preparation of cooperation agreements, the implementation of cooperation plans, and evaluation. Projects implemented by PKBM include equity projects. The model of cooperation that is carried out is assistance and guidance in the form of policy and regulatory support, legal protection, budget assistance, assistance, and motivating the community. The scheme for increasing community participation in education carried out by the village government involves community outreach, intervention, and evaluation.